Development of Clinical Pathway for Prevention and Control of Multidrug-Resistant Organisms Transmission in Hospital - Boonkirdram , Nattawipa; Picheansathian , Wilawan; Klunklin , Pimpaporn (Nursing Journal CMU, 2020)
Transmission of multidrug-resistant organisms in hospitals has a direct impact on patients, health care personnel, the hospital, community, and the nation. This developmental research aimed to develop a clinical pathway for prevention and control of multidrug-resistant organism transmission in the medical department at a regional hospital during October 2015 to January 2016. Study samples included 131 health care personnel who worked in the medical department and related units. Ten patients infected or suspected of multidrug-resistant organism infection and admitted at the medical department were included in the test using the clinical pathway implementation process. The process for developing the clinical pathway was based on the framework of Cheah. Three development steps were included: 1) assessing and analyzing the situation, 2) designing the clinical pathway, and 3) testing the implementation of clinical pathway. The data collection instruments consisted of a demographic data record form and questionnaire assessing the opinions of health care personnel towards the use of the clinical pathway. The content validity of the questionnaire was examined by 5 experts and the content validity index was .90. Data were analyzed using descriptive statistics and data categorization. The results revealed that the clinical pathway for prevention and control of multidrug-resistant organisms included: screening, using contact precautions, wearing masks, cleaning patients’ bodies with 2% Chlorhexidine gluconate, cleaning the environment, reminding the health care personnel, proper transfer of patient between units, active surveillance, and being careful of medical errors and adverse events. Most health care personnel agreed that this clinical pathway was clear, convenient, practical and appropriate for implementation in their units. This research suggests that this clinical pathway for prevention and control of multidrug-resistant organisms should be routinely implemented in the hospital.